Analysis of The Causes of Pending in JKN Claims For Outpatients at Orthopedic Hospital Prof. Dr. R. Soeharso Surakarta - Nurherawati, Umi; Hastuti, Nunik Maya; Mahmudah, Mutik; Bhoko, Coelestina Astri (Procedia of Engineering and Life Science, 2024)
Based on a preliminary survey at RS Ortopedi Prof. Dr. R. Soeharso Surakarta in the third quarter of 2023, outpatient JKN claims were pending with a percentage of 5.02% or 938 of the total submission of 18,703 medical records. The aim of the research was to determine the factors causing pending JKN claims for outpatients in the fourth quarter at RS Ortopedi Prof. Dr. R. Soeharso Surakarta. This type of research uses descriptive research with a cross sectional approach. This research was carried out to the JKN outpatient claims section at RS Ortopedi Prof. Dr. R. Soeharso Surakarta from February to April 2024. The subjects in this research were coding officers, INA-CBG's data entry officers, and internal verification officers at RS Ortopedi Prof. Dr. R. Soeharso Surakarta with the research object being the JKN outpatient claim file in the fourth quarter of 2023. Observation guide and an interview guide were used as the research instrument. The data were analyzed using processing techniques used are collecting, editing, tabulation and data presentation. Descriptive data analysis techniques. The research results show the percentage of pending JKN claims for outpatients in the fourth quarter of 2023 at RS Ortopedi Prof. Dr. R. Soeharso Surakarta amounted to 2.04% with a total of 396 pending claims for medical records with a total of 19,399 medical records submitted. The highest cause of pending is in the administrative aspect. Result of the research shows the percentage of pending JKN claims for outpatients in the fourth quarter of 2023 at RS Ortopedi Prof. Dr. R. Soeharso Surakarta is 2.04% with the number of 396 pending files from 19,399 medical records submitted. Therefore, officers are more careful in inputting patient information and completeness of files before submission and maximizing.